"Der deutsch-slowakische Staatsvertrag unterzeichnet". V.l.n.r. Czernak, von Ribbentrop und Schmidt
"Der deutsch-slowakische Staatsvertrag unterzeichnet". V.l.n.r. Czernak, von Ribbentrop und Schmidt.